RESPONSE OF CHINA ASTER (CALLISTEPHUS CHINENSIS L.) GENOTYPES TOWARDS FOLIAR APPLICATION OF GA3 (American International Journal of Agricultural Studies, 2021)
China Aster is one of the most popular flower that are used in ornamental garden. The demand for cut flowers of China aster is increasing day by day, but it has not been possible to supply the adequate amount of flowers especially during the festival season. The area under flower production is increasing year after year but farmers are not getting quality seeds in adequate quantity as very few farmers are taking up seed production because flower seeds loose their viability earlier than crop seeds. So, production of adequate quantity of quality seeds is essential to meet the demand. The present investigation was undertaken in Horticulture Research Station, Mondouri, B.C.K.V., Mohanpur, Nadia, West Bengal during Rabi season of 2018-19 and 2019-20.  Over two consecutive years, six genotypes were evaluated the potentiality of for its growth and flowering, as well as to estimate the influence of GA3 through foliar application at pre-flowering stage on its seed production. In field three treatments were considered viz. T1 (control i.e.no application of GA3), T2 (GA3@50ppm), T3 (GA3@100ppm). According to the size of flowers, highest was recorded in Local Mix (G6). So, it could be considered as the best performer genotype considering flower diameter. Seed yield plant-1 was recorded highest in Local White (G5), it could be considered as the best performer genotype considering its higher number of flowers plant-1 and number of seeds flower-1. GA3 (100 ppm) could be utilized in a better way for greater enhancement in all those important parameters as overall influence of GA3 has been found to improve seed yield plant-1 and all the important attributes. Concomitant consideration of seed yield and its important attributes may indicate to recommend foliar application of 100 ppm GA3 for enhancement in seed yield in all the genotypes. Similar to the seed yield and its attributes, plant growth and development have been noticed to be positively influenced by GA3 concentrations with a higher side after 100 ppm, may lead to recommend foliar application of 100 ppm GA3 for commercial cultivation of this crop irrespective of the genotypes.